The Promotion Strategies in Improving the Small Industry Markets for Fish Processing - Fajar Pasaribu; Widia Astuty (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Small-scale fish processing industry is a marine fish processing activity which is widely available in District of Central Tapanuli. This research aims to give thought contribution to marketing management of small fish processing industry to make breakthrough to unclear and uncertain the implementation of product strategy, price, distribution, and promotion. The scope of the research includes a survey of marine fish processing entrepreneurs. The population in this study is 153 small fish processing entrepreneurs in 6 districts in Central Tapanuli consists of Pandan, Tapian Nauli, Badiri, Sorkam, West Sorkam and Barus sub-districts. The analysis was conducted by multiple regression model and hypothesis testing was conducted by ttest for partial test, and Ftest test for simultaneous test. The results showed that partially the implementation of product, distribution and promotion strategy had positive effect; meanwhile the price strategy had a negative effect to the market share of small fish processing industry in the District of Central Tapanuli. Furthermore, the simultaneous implementation of product strategy, price, distribution, and promotion has a positive effect to the market share of small fish processing industry in the District of Central Tapanuli.